TiO2/SiO2 optical filters based on fabry-perot resonators for endoscopy - Silva, M. F. (2012)
This paper presents the design, simulation and characterization of two Fabry-Perot thin-film resonators composed by thin-films of titanium dioxide (TiO2) and silicon dioxide (SiO2). The two optical filters are developed for integration on top of light-emitting diodes (LEDs) to perform narrow band imaging (NBI) diagnosis in endoscopy. The NBI is a high-resolution imaging technique that uses light spectral centered on 415 nm (blue) and 540 nm (green). Classical endoscopes and endoscopic capsules (EC) use white light for acquiring images of the gastrointestinal tract (GI). Commercially available blue LED has maximum intensity at 402 nm and the green LED at 522 nm. The simulations present a maximum spectral transmittance for the blue LED + Fabry-Perot resonator of 21 % centered at 415 nm with Full-Width-Half-Maximum (FWHM) of 16 nm. The green LED + Fabry-Perot resonator has maximum spectral transmittance of 33 % centered at 436 nm with a FWHM of 32 nm.